Penerapan Pembelajaran Pendidikan Pancasila dan Kewarganegaraan pada Anak Usia Dini - Aisya, Talitha Nabilah; Ni’mah, Nina Kayatun; Amelia, Lina; Cahya, Tirta Nur (TSAQOFAH, 2024)
Pancasila and citizenship education is a learning whose fulcrum is to develop Pancasila values as the basis of the Indonesian state. However, apart from that, Pancasila and citizenship education is also learning that focuses on providing moral values and rules in life as a citizen and in society. In practice, this education must be taken from elementary school children to tertiary institutions. Therefore, the basis for this education must be implemented from an early age. This is because young children are in a phase where their cognitive development can reach 80% of their life. In maximizing this development, the provision of Pancasila and citizenship education must begin to be instilled from childhood, by providing lessons regarding Pancasila education in a simpler way according to their age concept so that children get used to carrying out habits which contain elements of Pancasila. . The method used in making this journal is a literature study from several journals and books about Pancasila education and education carried out at the early childhood level.